2014
DOI: 10.1111/arcm.12118
|View full text |Cite
|
Sign up to set email alerts
|

RHX Dating: measurement of the Activation Energy of Rehydroxylation for Fired‐Clay Ceramics

Abstract: In rehydroxylation (RHX)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…The data used by H2011 indicate a high variability in the exponent values of 1/ N , similar to that observed in archeological fired‐clay ceramic artifacts . It is worth mentioning that this variability does not originate from the energy of activation characterizing each studied sample . It is possible that the 1/ N value is an intrinsic property of the earthenware, depending on the nature of clays and/or on the temperature reached during the original firing of the ceramics.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The data used by H2011 indicate a high variability in the exponent values of 1/ N , similar to that observed in archeological fired‐clay ceramic artifacts . It is worth mentioning that this variability does not originate from the energy of activation characterizing each studied sample . It is possible that the 1/ N value is an intrinsic property of the earthenware, depending on the nature of clays and/or on the temperature reached during the original firing of the ceramics.…”
Section: Resultssupporting
confidence: 61%
“…8 It is worth mentioning that this variability does not originate from the energy of activation characterizing each studied sample. 9,17 It is possible that the 1/N value is an intrinsic property of the earthenware, depending on the nature of clays and/or on the temperature reached during the original firing of the ceramics. It may also be possible that the experimental conditions (temperature, relative humidity) have some influence on the underlying process.…”
Section: Discussionmentioning
confidence: 99%
“…The temperatures are measured in kelvin (K). The activation energy is the minimum energy required to start the chemical reaction . The universal gas constant is R = 8.3144621 J·(K·mol) −1 .…”
Section: Determination Of the Activation Energymentioning
confidence: 99%
“…The samples may come, for example, from the same archeological stratum; provided by an archeologist who determines, based on excavation information, that they have the same age. Clelland et al . found that even ceramic sherds broken from some particular plates had activation energies that differed significantly from one another.…”
Section: Determination Of the Effective Lifetime Temperature And Rhx Agementioning
confidence: 99%
See 1 more Smart Citation